Rice biofortification with zinc and selenium: a transcriptomic approach to understand mineral accumulation in flag leaves - Roda, Faustino Adriano; Marques, Isabel; Batista-Santos, Paula; Esquível, Maria Glória; Ndayiragije, Alexis; Lidon, Fernando Cebola; Swamy, B.P. Mallikarjuna; Ramalho, José Cochicho; Ribeiro-Barros, Ana I. (Frontiers Media, 2020)
Human malnutrition due to micronutrient deficiencies, particularly with regards to Zinc (Zn) and Selenium (Se), affects millions of people around the world, and the enrichment of staple foods through biofortification has been successfully used to fight hidden hunger. Rice (Oryza sativa L.) is one of the staple foods most consumed in countries with high levels of malnutrition. However, it is poor in micronutrients, which are often removed during grain processing. In this study, we have analyzed the transcriptome of rice flag leaves biofortified with Zn (900 g ha–1), Se (500 g ha–1), and Zn-Se. Flag leaves play an important role in plant photosynthesis and provide sources of metal remobilization for developing grains. A total of 3170 differentially expressed genes (DEGs) were identified. The expression patterns and gene ontology of DEGs varied among the three sets of biofortified plants and were limited to specific metabolic pathways related to micronutrient mobilization and to the specific functions of Zn (i.e., its enzymatic co-factor/coenzyme function in the biosynthesis of nitrogenous compounds, carboxylic acids, organic acids, and amino acids) and Se (vitamin biosynthesis and ion homeostasis). The success of this approach should be followed in future studies to understand how landraces and other cultivars respond to biofortification.